Plant growth, stress tolerant traits and regulation of heat activated proteins in Aspalathus linearis (Burm. f.) R. Dahlgren exposed to elevated temperature and drought - MacAlister, Dunja (Department of Biological Sciences, 2022)
Climate change is increasingly becoming a concern on plant growth, as seen in the increased number of warmer days and nights as well as an increased occurrence of heat waves, and drought periods globally. The Intergovernmental Panel on Climate Change has stated that global surface temperatures are constantly increasing and are likely to exceed 2 °C, compared to average temperatures in 1900, by the end of the 21st century. Changes in precipitation will also become more erratic, with high latitude and mid-latitude areas expected to have increases and decreases in rainfall respectively, while already dry areas will have increased frequencies of drought. Regions with Mediterranean climates, such as the Western Cape in South Africa, are particularly vulnerable to these climate impacts, with models and studies showing that there are already significant increases in temperatures, shifts in later winter rainfall and an increased severity of flooding. These climatic changes will impact both natural and agricultural plant species growth and distribution due to the changes in suitable growing conditions and regions. Plants are already exposed to a wide variety of environmental factors, each of which influences the growth, and deviations from the optimal conditions is considered abiotic stress and negatively affects plant growth. Plants in the field are rarely affected by only one stress as they are frequently exposed to a combination of abiotic stresses and with the changes in climate, plants will likely be experiencing abiotic stress such as heat and drought stress simultaneously. The aim of this thesis was to determine the effects of heat and drought on the plant growth and physiological performance of one of the most important indigenous commercial crops in South Africa, Aspalathus linearis (Burm.f.) R. Dahlgren, better known as rooibos tea, known for its many health benefits. This was achieved by focusing on three objectives: (1) determining the effects of temperature on plant growth and identifying the thermotolerant traits of the plants grown in the field along a temperature gradient, (2) determining the heat activated proteins and associated mechanisms for heat tolerance in field grown plants and (3) determining the physiological and morphological responses of A. linearis grown under two moisture regimes and later exposed to drought. The results for objective one are presented in chapter two, where a field study was conducted to observe the effects of temperature on the growth and stress tolerant traits of A. linearis grown at four farms sites in the Cederberg, South Africa along a temperature gradient. The four sites represent the rooibos farming area, from coolest to warmest respectively; Aurora (alt. 93 m), Citrusdal (alt. 588 m), Clanwilliam (alt. 312 m) and Uitsig (alt. 344 m). Aurora was also situated closest to the coastline, ∼18 km, compared to the other farms. The traits observed were changes in gas exchange, carbohydrate concentrations, phenolics and pigments, along with biomass, over a two-year period. Aspalathus linearis plants showed evidence of transpirational leaf cooling during summer and this, combined with lower chlorophyll and high phenolic content, could be considered acclimatized adaptive changes allowing the plants to mitigate the heating effects of elevated temperatures. Chapter three presented the results for objective two where the proteome of A. linearis was analysed from field plants along a temperature gradient. Protein samples were collected from the plants concurrently with the physiological samples for the previous chapter. These protein samples were quantified and then functionally annotated using the OrthoDB and UniProt databases. Overall, a total of 180 proteins were differentially expressed in the plants during exposure to high temperatures in the field. Of these 180 proteins, 113 were more upregulated in the cooler sites, Aurora and Citrusdal, and 67 proteins were more upregulated in the hotter sites, Clanwilliam and Uitsig thus indicating that with increasing temperatures there is a downregulation of proteins expressed during heat stress. From the 180 proteins, there were six main proteins involved in photosynthesis or light harvesting in A. linearis, with four of the six proteins upregulated in plants grown at Aurora, the cooler site, and in the hottest site, Uitsig. This agrees with results from chapter two, where plants from Aurora had superior photosynthetic rates compared to the other plants therefore allowing them to grow and produce better biomass. The hotter sites upregulated heat shock proteins more than the cooler sites, suggesting that their expression could be enhancing the thermotolerance of A. linearis plants through their chaperone activity where they protect other proteins against denaturation. There were also numerous proteins expressed in the plants which were related to oxidationreduction processes and antioxidants, most of which were expressed in the hottest site, Uitsig. One of the main concerns for plants during heat stress is the oxidative damage brought on by reactive oxygen species, and the expression of these proteins indicates that these proteins are contributing to the plants' thermotolerance through the production of antioxidant phenolic compounds as was seen in chapter two. In chapter four, a glasshouse study was conducted where plants were grown at two different moisture regimes (field capacities, FC) and then exposed to drought and both physiological and morphological parameters were measured. Morphological parameters measured included plant biomass, root/shoot ratios, total root length, average root diameter, total root surface area and specific root length. Physiological parameters measured were gas exchange, carbohydrate and phenolic concentrations, pigment concentrations, leaf relative water content and water potential. During drought, the gas exchange, relative water content and nonstructural carbohydrates in leaves were all reduced, while chlorophyll concentrations remained constant. Aspalathus linearis plants also had reduced stomatal conductance and transpiration, increased root/shoot ratios, root length and antioxidants such as polyphenol in leaves under drought conditions. Overall, changes in soil nutrients, including boron, available phosphorus, manganese and copper, and increasing temperatures had a negative impact on crop biomass, however, the phenolic content, which is a measure of tea quality, did not vary with sites. This suggests that farmers who are planning on shifting their rooibos farming further south of Cederberg, could still achieve good growth and high yields without compromising the quality of the tea. It was also seen that A. linearis plants upregulated heat shock proteins, along with proteins involved in antioxidant compounds particularly in the hotter sites thereby playing a critical role in their acquired heat-stress tolerance. Plants in the cooler sites upregulated proteins involved in photosynthesis and chlorophyll production, therefore allowing them to have higher photosynthetic activity and subsequently higher productivity. The up and down regulation was based on comparing the warmer sites (heat-stressed) to the cooler sites (control). The plants grown at lower FC and then droughted, exhibited drought tolerant mechanisms which included higher root/shoot ratios as well as thinner roots, both of which are effective for water and nutrient uptake. Overall, plants in the 30 % FC treatment recorded lower Pmax, gs and E after three days in the drought conditions while 70 % FC plants were only affected after five days. Furthermore, plants grown under low moisture (30 % FC) conditions produced 50 % lower biomass compared to plants grown under adequate moisture (70 % FC) conditions. This implies that low rainfall and the occurrences of dry spells and drought, associated with climate change are likely to reduce the production of A. linearis in the Cederberg area. The combination of both field work and glasshouse studies have provided insight into how these plants are affected by both heat and drought stress, as well as declining soil nutrients such as calcium, magnesium, manganese iron, copper and potassium. Aspalathus linearis is tolerant to high temperatures as well as dry conditions, however, more needs to be explored with regards to their thresholds particularly since climate change is likely to continue in the near future and eventually moving farming south will no longer be an option for farmers.